Research of opportunities for the ecosystem approach to career planning by students at the State University of Management - E. V. Krasnov; A. D. Rudoy; I. V. Semenov; E. V. Sumarokova (Вестник университета)
The article presents the results of studying the possibilities of an ecosystem approach to career planning by students at the State University of Management (hereinafter referred to as SUM). At first, the gap between the level of practical training of graduates of Russian universities and the requirements of employers has been actualised. Then, the need for joint efforts of all interested labour market participants to create conditions for students’ conscious planning of career growth at all stages of education is emphasised. The experience of intra-university cooperation using the STC (student team consulting) method between the marketing department and practical training department in 2022–2023 has showed that solving this problem involves integrating, on an ecosystem basis, activities for the study of professional academic disciplines, project-based learning, practical training, and employment. As an experiment, 6 student consulting teams have solved a set of interrelated tasks, including the creation and ongoing maintenance of the Career Centre page in the VK social network, advertising campaigns and interviews at “Career Day in Transport and Logistics”, surveys on the employment of graduates and assessment of student satisfaction with practical training, analytical review of the labour market in Russia in 2020–2023 with a report at the All-Russian scientific and practical conference, examination of 5 ideas for marketing research projects in the field of career planning by students of the SUM with testing in social networks and assessments of the influence of actors in its ecosystem. In conclusion, based on the results of the research, the directions for the ecosystem approach to career planning by students at the SUM are formulated.